An epidemiological extension of the El Farol Bar problem - Bertolotti, Francesco; Kadera, Niccolò; Pasquino, Luca; Mari, Luca (Frontiers in Big Data, 2025)
This paper presents an epidemiological extension of the El Farol Bar problem, where both a social and an epidemiological dimension are present. In the model, individual agents making binary decisions—to visit a bar or stay home—amidst a non-fatal epidemic. The extension of the classic social dilemma is implemented as an agent-based model, and it is later explored by sampling the parameter space and observing the resulting behavior. The results of this analysis suggest that the infection could be contained by increasing the information available in the underlying social system and adjusting its structure.